Effect of blade number on the performance of an H-rotor vertical axis wind turbine under low wind speed conditions - Agustinus Lolok; Lukas Kano Mangalla; Bahdin Ahad Badia (Jurnal Polimesin, 2026)
Vertical Axis Wind Turbines (VAWTs) have significant potential for small-scale wind energy applications, particularly in regions with low to moderate wind speeds. One of the key design parameters influencing VAWT performance is the number of blades. This study aims to experimentally investigate the effect of blade number on the operational characteristics and aerodynamic efficiency of a laboratory-scale vertical axis wind turbine. Three turbine configurations with 2, 3, and 4 blades were tested, each with a blade height of 25 cm and installed at 45 cm above the ground. Experiments were conducted using an axial fan with a flow straightener in a laboratory setup under wind speeds of 2, 3, 4, and 5 m/s. Measured parameters included rotational speed (RPM), torque, mechanical power, Tip Speed Ratio (TSR), and power coefficient (Cp). The results indicate that the three-bladed turbine exhibits the best overall performance, achieving a maximum power coefficient of 0.37 at a wind speed of 5 m/s and a TSR of approximately 2.2. A relative efficiency analysis confirms that the three-bladed configuration offers the most favorable balance among torque generation, rotational speed, and aerodynamic losses. These findings offer valuable insights for optimizing small-scale VAWT design and enhancing wind energy utilization in low-wind-speed environments.